The implementation effect of realistic mathematics education and contextual teaching and learning approaches on the students' mathematical communication ability: A meta-analysis - Putri, Nurmala Setianing; Juandi, Dadang; Jupri, Al (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Over the last ten years, many studies have discussed the effect of implementing the Realistic Mathematics Education (RME) and Contextual Teaching and Learning (CTL) approaches on students' mathematical communication ability. However, these studies show inconsistent results. This study aims to analyze the effect of implementing the RME learning approach, the effect of implementing the CTL approach, and the difference in the effect of implementing the RME learning approach compared to the CTL approach on students' mathematical communication ability. This research used a quantitative approach with a meta-analysis method. The search for research articles with publication years from 2012 to 2022 was carried out using several databases, namely DOAJ, ERIC, Google Scholar, IOP Publishing, Garuda Portal, Semantic Scholar, and national journals link. Using the PRISMA protocol, the authors obtained 15 research articles on RME and 14 research articles on CTL that met the inclusion criteria and could be used in this study. The results of this study showed that the implementation of the RME learning approach has a moderate influence (g = 0,820) on students' mathematical communication ability, and the implementation of the CTL approach has a strong influence (g = 1,017) on students' mathematical communication ability. There is no significant difference between the effect of the RME learning approach's implementation and the CTL approach's effect on students' mathematical communication ability (Q_value = 2,329, p_value = 0,127). Therefore, the RME and CTL learning approaches can be used as learning alternatives that aim to enhance students' mathematical communication ability.